1999
DOI: 10.4049/jimmunol.162.12.7256
|View full text |Cite
|
Sign up to set email alerts
|

IL-12 Induces IFN Regulating Factor-1 (IRF-1) Gene Expression in Human NK and T Cells

Abstract: IL-12 is a critical immunoregulatory cytokine that promotes cell-mediated immune responses and the differentiation of naive CD4+ cells to Th1 cells; however, relatively few IL-12 target genes have been identified. To better clarify the molecular basis of IL-12 action, we set out to characterize genes up-regulated by IL-12, first by contrasting IL-12- and IFN-α-inducible genes. We identified several genes up-regulated by IL-12, namely, MIP-1α, MIP-1β, IL-1RA, and IFN regulatory factor-1 (IRF-1). IRF-1 is a tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…In fact, the highest densities of adaptive immune cells were observed in the earliest tumors stages [21,47]. These indicated that adaptive immunity, including cytotoxic CD8 T-cells and helper CD4 T-cells with Th1 signature (IFNG, IL12, IRF1) [48], might arise before the carcinoma stage. We recently validated this hypothesis, showing adaptive immune infiltration, increased adaptive immunity, as well as immune escape mechanisms, including immune checkpoint, in precancer lesions [49].…”
Section: Discussionmentioning
confidence: 93%
“…In fact, the highest densities of adaptive immune cells were observed in the earliest tumors stages [21,47]. These indicated that adaptive immunity, including cytotoxic CD8 T-cells and helper CD4 T-cells with Th1 signature (IFNG, IL12, IRF1) [48], might arise before the carcinoma stage. We recently validated this hypothesis, showing adaptive immune infiltration, increased adaptive immunity, as well as immune escape mechanisms, including immune checkpoint, in precancer lesions [49].…”
Section: Discussionmentioning
confidence: 93%
“…STAT1 activation could induce inducible nitric-oxide synthase (iNOS), a hallmark of renal ischemia–reperfusion injury and oxidative stress. Similarly, IL-12α potentiates IFN-γ-mediated signal transduction by inducing the secretion of IFN-γ in different cell types [ 57 ]. Therefore, we evaluated the effects of 18 h CS + Tx on the expression of IFN-γ, IL-12α, iNOS, and endothelial nitric oxide synthase (eNOS) genes in renal grafts.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we showed that CS + Tx activates STAT1 and STAT3 factors and increases STAT1 protein levels within transplanted kidneys. Phosphorylation of STAT1 at Y701 is required for transcriptional activation of STAT1 [ 45 , 56 , 57 , 58 , 59 , 60 , 61 ], and this activation induces cell cycle/growth arrest and promotes apoptosis [ 62 , 63 , 64 , 65 , 66 ]. Similarly, phosphorylation of STAT3 at Y705 is required for transcriptional activation of STAT3 [ 61 , 67 , 68 ], and in most instances, this activation induces cell growth/proliferation that promotes cell survival [ 69 , 70 , 71 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IRF1 has been tied to B and T lymphocyte and myeloid cell development and function (22)(23)(24)(25)(26)(27)(28)(29). Irf1 transcript levels increase during myeloid differentiation and in response to external stimuli, including viral infections, lipopolysaccharide (LPS), type I and type II IFNs, interleukin-1 (IL-1), IL-12, and granulocyte colony-stimulating factor (12,(30)(31)(32)(33)(34)(35)(36)(37). IRF1-deficient mice exhibit altered immune cell populations, with decreased numbers of peripheral blood (PB) CD8 + T and natural killer (NK) cells, concomitant with increased numbers of CD4 + T cells (28,29), and unaltered levels of red blood cells (RBCs) (38).…”
Section: Introductionmentioning
confidence: 99%